Решите уравнения: 1. x^2=8x-17 2. 14x=-49-x^2 3. 36+17x=-2x^2 4. 7x^2-3x=4 5.6x=9x^2=-1 6. 0.81-x^2=0 7. 5x+9x^2=0 8.1+2x=8x^2 9. 19x-6x^2-10=0 10. 8+2x^2=0 11. 40x-25-16x^2=0 12. -36-x^2=-12x

Решать построчно

2

Ответы и объяснения

2013-01-24T12:42:57+04:00

 x^2=8x-17

 x^2-8x+17=0

Д=(-8)^2-4*17=64-68 <0

 

14x=-49-x^2

X^2+14x+49=0

D=14^2-4*49=196-196=0

x=-14/2=-7

 

36+17x=-2x^2

2x^2+17x+36=0

D=17^2-4*2*36=289-288=1

x1=-17+1/4=-16/4=-4

x2=-17-1/4=-18/4

 

7x^2-3x=4

7x^2-3x-4=0

D=-3^2+4*7*4=9+112=121=11^2

x1=3+11/14=1

x2=3-11/14=-8/14

 

 

 

 0.81-x^2=0

-x^2=-0.81

x^2=0.81

x=+-0.9

 

 5x+9x^2=0

9x^2+5x=0

x(9x+5)=0

x=0  9x=-5

          x=-5/9

 

1+2x=8x^2

-8x^2+2x+1=0

D=2^2+4*8=4+32=36=6^2

x1=-2+6/-16=-1/4

x2=-2-6/-16=1/2

 

19x-6x^2-10=0

-6x^2+19x-10=0

D=19^2-4*6*10=361-240=121=11^2

x1=-19+11/-12=-8/-12=2/3

x2=-19-11/-12=2.5

 

8+2x^2=0 

2x^2=-8

x^2=-4 нет корней

 

40x-25-16x^2=0 

-16x^2+40x-25=0

D=40^2-4*16*25=1600-1600=0

x=-40/-32=10/8=5/4

 

-36-x^2=-12x

-x^2+12x-36=0

D=12^2-4*36=144144=0

x=-12/-2=6

  • miad
  • светило науки
2013-01-24T13:02:07+04:00

1. x^2-8x+17=0

Дискриминант: D=64-4*17=64-68=-2<0 Корней нет

 

2. x^2+14x+49=0 \ \ \ \ \ \ \ \ (x+7)^2=0 Корень один х=-7

 

3. 2x^2+17x+36=0

Дискриминант: D=289-4*2*36=289-288=1

x_{1;2}=\frac{-17 \pm 1}{2*2} \ \ \ \ \ \ \ \ x_1=-4 \ \ \ \ \ x_2=-4.5

 

4. 7x^2-3x-4=0

D=9-4*7*(-4)=9+112=121

x_{1;2}=\frac{3 \pm 11}{2*7} \ \ \ \ \ \ \ \ x_1=1 \ \ \ \ \ x_2=-4/7

 

5. 9x^2+6x+1=0

D=36-36=0

x=\frac{-6 \pm 0}{2*9}=-\frac{1}{3}

 

6. x^2=0.81

x_{1;2}=\pm \sqrt{0.81}=\pm0.9

 

7. 9x^2+5x=0

 x(9x+5)=0 \ \ \ \ \ \ \ x_1=0 \ \ \ \ \ \ \ x_2=-5/9

 

8. 8x^2-2x-1=0

D=4+32=36

x_{1;2}=\frac{2 \pm 6}{2*8} \ \ \ \ \ \ \ \ x_1=0.5 \ \ \ \ \ x_2=-0.25

 

9. 6x^2-19x+10=0

D=361-4*6*10=361-240=121

x_{1;2}=\frac{19 \pm 11}{2*6} \ \ \ \ \ \ \ \ x_1=2.5 \ \ \ \ \ x_2=2/3

 

10. 2x^2=-8

x^2=-4 Корней нет, т.к. x^2\geq0

 

11. 16x^2-40x+25=0

(4x)^2-2*4*5x+5^2=0

(4x-5)^2=0

x=5/4=1.25

 

12. x^2-12x+36=0

x^2-2*6x+6^2=0

(x-6)^2=0

x=6